Shelf-life of Extra Virgin Olive Oils from Southern Italy - Barbarisi, Costantina; Di Stasio, Michele; La Cara, Francesco; Nazzaro, Melissa; Siano, Francesco; Coppola, Raffaele; Volpe, Filomena; De Mattia, Anna; Grazia Volpe, Maria (Current Nutrition & Food Science, 2014)
This study investigated the effect of a 12 months storage period on quality, biochemical, and chemical parameters of three extra virgin olive oils (mono-cultivars Ortice and Ravece, and Bonito, a mix of different cultivars). Based on their free acidity, peroxide index, and spectrophotometric indices, all three analyzed oils produced values within the range of classification as “extra virgin olive oil”. The content of total polyphenols, tyrosol, and hydroxytyrosol progressively decreased during their storage period in all varieties of oil, leading to deterioration in quality as a consequence of oxidative and hydrolytic degradations. The concentration of Fe, Cu, Mn, and Zn decreased in the oils during the storage period, while it increased in the sediment that formed in the containers.
Keywords: polyphenols